Over a million students use our free study notes to help them with their homework
2y dy/dx - x dy/dx - y + 6x = 0dy/dx (2y-x)= y-6xdy/dx= (y-6x)/(2y-x)
Looking at the problem to start we can see that this is an algebraic division problemThere are three common methods you will come across for finding dy/dx for algebraic problems: The Chain Rule, The Produ...
Note: I have a screenshot of the question that I should be able to add to the work space. Q5 C4 June 2014 Edexcel.x + y = 2sqrt(3) cos tStart with x = 4 cos ( t + pi/6) and the trig identity cos(A + B) = ...
Starting from the left hand side we can substitute the sin and cos sum and difference formulas. These are sin(A+B) = sinAcosB + cosAsinBand cos(A+B) = cosAcosB - sinAsinBBecause x = A = B when substituted...
First we should try and factorise the polynomial the brackets will be (x+?) and (x-?) as the coefficient of x and the -21 have differing signs.just thinking of the factors of 21 we can see that 7-3 = 4 th...
←
256
257
258
259
260
→
Internet Safety
Payment Security
Cyber
Essentials